2022
DOI: 10.3389/fenvs.2022.787204
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Green City Concept in the Tropical and Global South Cities Context: The Case of Indonesia

Abstract: Urban areas play a key role in reaching global sustainability as they produce a high amount of waste and emissions, consume a lot of resources, and perform as the prime mover of the global economy. Unsustainable urbanization will generate multidimensional impacts on the earth’s socio-ecological system that is nearly impossible to be managed. As a preemptive action, urban sustainability has been considered as one of the most important targets in the Sustainable Development Goals. Within this context, the green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 63 publications
(74 reference statements)
1
10
0
1
Order By: Relevance
“…Therefore, green open spaces should be site-specific and include native plant species, which have adapted to the local environment. Plant health is essential to environmental health, hence green areas should be well maintained (Zain et al, 2022). Next, involve communities in decision-making.…”
Section: Recommendations To Enhance Green Open Space Governance In In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, green open spaces should be site-specific and include native plant species, which have adapted to the local environment. Plant health is essential to environmental health, hence green areas should be well maintained (Zain et al, 2022). Next, involve communities in decision-making.…”
Section: Recommendations To Enhance Green Open Space Governance In In...mentioning
confidence: 99%
“…This step could be done by doing collaboration. Since, lack of intersectoral collaboration and institutional fragmentation has consequently diminished the definition of a green city in Indonesia (Zain et al, 2022).…”
Section: Recommendations To Enhance Green Open Space Governance In In...mentioning
confidence: 99%
“…For example, the Trans Java Expressway development in Indonesia aimed to spur interregional connectivity and economic growth in a ''green way'' but has increased the vulnerability of cities located along the coastline to flooding and land subsidence. 7 Considering that 100 unintended consequences were identified for UK housing energy-efficiency policies alone, 8 it is vitally important that local policymakers be enabled to assess climate solutions more systemically.…”
Section: Understanding Cities As Complex Systemsmentioning
confidence: 99%
“…The element of smart environment must also be a top priority to prevent environmental damage that could occur during the construction of the new capital city. By establishing data disclosure, smart environments can support efforts to implement green cities by focusing on local socio-ecological conditions and community engagement in addition to providing green open spaces (Amalia et al, 2020;Rusadi et al, 2016;Zain et al, 2022). Previous research has demonstrated that implementing the concept of a smart city can increase urban eco-efficiency by 16%-18% (Yao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%